Profiling of how nociceptor neurons detect danger – new and old foes. (29th July 2019) - Crosson, T.; Roversi, K.; Balood, M.; Othman, R.; Ahmadi, M.; Wang, J.‐C.; Seadi Pereira, P. J.; Tabatabaei, M.; Couture, R.; Eichwald, T.; Latini, A.; Prediger, R.D.; et al.
Abstract: The host evolves redundant mechanisms to preserve physiological processing and homeostasis. These functions range from sensing internal and external threats, creating a memory of the insult and generating reflexes, which aim to resolve inflammation. Impairment in such functioning leads to chronic inflammatory diseases. By interacting through a common language of ligands and receptors, the immune and sensory nervous systems work in concert to accomplish such protective functions. Whilst this bidirectional communication helps to protect from danger, it can contribute to disease pathophysiology. Thus, the somatosensory nervous system is anatomically positioned within primary and secondary lymphoid tissues and mucosa to modulate immunity directly. Upstream of this interplay, neurons detect danger, which prompts the release of neuropeptides initiating (i) defensive reflexes (ranging from withdrawal response to coughing) and (ii) chemotaxis, adhesion and local infiltration of immune cells. The resulting outcome of such neuro‐immune interplay is still ill‐defined, but consensual findings start to emerge and support neuropeptides not only as blockers of TH 1‐mediated immunity but also as drivers of TH 2 immune responses. However, the modalities detected by nociceptors revealed broader than mechanical pressure and temperature sensing and include signals as various as cytokines and pathogens to immunoglobulins and even microRNAs. Along these lines, we aggregated various dorsal root ganglion sensory neuron expression profiling datasets supporting such wide‐ranging sensing capabilities to help identifying new danger detection modalities of these cells. Thus, revealing unexpected aspects of nociceptor neuron biology might prompt the identification of novel drivers of immunity, means to resolve inflammation and strategies to safeguard homeostasis. Abstract : Content List ‐ Read more articles from the symposium: "Bioelectronic Medicine: Technology targeting molecular mechanisms".